Factors associated with human immunodeficiency virus infection and self-assessed risk to human immunodeficiency virus among injecting drug users in Manipur, India - Balasubramanian Ganesh; Kriina Mosoniro; Joshua Vasna; Arumugam Elangovan; Aridoss Santhakumar; Rajan Shobini (Wolters Kluwer Medknow Publications, 2020)
Background: The proximity of Northeast India to the Golden Triangle facilitates easy accessibility to illicit drugs, resulting in a higher proportion of injecting drug users (IDUs) in the states of Northeast India. The estimated human immunodeficiency virus (HIV) prevalence among IDU in Manipur which is 1.43% is higher than that of the national figure. Objectives: The objectives of the study were to find the factors associated with HIV infection and correlate the association between HIV status and self-assessed risk to HIV among IDUs in Manipur. Methods: National Integrated Biological and Behavioral Surveillance (2014-2015) data were used for the study; all analyses done were weighted. In Manipur, information was collected from 1594 IDUs during the surveillance between 2014 and 2015 across four domains, namely Chandel (396), Imphal East (397), Thoubal (401), and Senapati (400). Chi-square test was performed to test the association between the independent and dependent variables. Multivariable logistic regression was performed to identify risk factors associated with HIV positivity. Results: Higher age, unsafe injecting practice, low education status, and low-income status were significantly (P < 0.05) associated with HIV infection among IDUs in Manipur. Self-assessed risk of HIV infection by IDU was significantly associated with HIV positivity. Conclusion: Interventions among IDUs in Manipur should focus on emphasizing safe injecting practices along with creating awareness on HIV prevention and management.